Performing ignorance of state violence in Aotearoa New Zealand - Stanley, Elizabeth (Journal of criminology, 2024)
In 2019, the New Zealand government established a Royal Commission of Inquiry into Abuse in Care to investigate the abuse and neglect of children, young people and vulnerable adults in Aotearoa/New Zealand between 1950 and 1999. The public hearings, witness statements and interim reports have charted horrific violence by state and faith-based workers including torture, sexual assaults, serious physical violence, and layers of neglect and discrimination. Māori have been especially targeted as victims of abuse and harms. This article considers the multiple layers of ignorance-making from state representatives. It shows how state agencies have navigated Commission hearings through 10 strategies that demonstrate some acknowledgement of their offending and trauma-making while simultaneously minimising their responsibility and resecuring their institutional legitimacy as protectors of the vulnerable and saviours of Te Tiriti (the Treaty of Waitangi), ethics and integrity. This careful performance stands at odds with the ongoing layers of violence and harms in state care.